DESIGN AND CONSTRUCTION OF A HYDRAULIC RAM PUMP - Encu Shobari; Alwi Albaar (Jurnal Mekanika dan Manufaktur, 2026)
Areas whose land surface lies higher than the available water source often face difficulty obtaining a continuous water supply. Using an electric pump to lift water under such conditions increases operational costs because it depends on electrical energy, so an alternative technology is needed that can raise water from a lower to a higher elevation without fuel or electricity. This study aims to design and construct a hydraulic ram pump as a solution for community water needs in Argalingga Village, Argapura Subdistrict, Majalengka Regency, where the elevation difference between the water source and the settlement is approximately 21 m with a distance of about 100 m. Concept selection was carried out using the Analytic Hierarchy Process (AHP) on five design alternatives based on price, working performance, ease of use, maintenance, and service life criteria, with the hydram pump selected as the alternative with the highest final weight (0.290). The pump was constructed from PVC pipe with a 2-inch pump body diameter, a 3-inch delivery tank, and a 2-inch input pipe. Testing was conducted using five variations of input height and input pipe length. Results show that at an input height of 1 m and input length of 8 m, a maximum output height of 13 m was achieved with a discharge of 1.20 L/min; at 1 m and 12 m, output height 13 m with 1.71 L/min; at 2 m and 16 m, output height 17 m with 1.89 L/min; at 2 m and 20 m, output height 17 m with 3.00 L/min; and after extending the output pipe length at the 2 m/20 m configuration, a maximum output height of 21 m with a discharge of 2.12 L/min was obtained. These results indicate that increasing the input height and input pipe length improves both the lifting height and discharge output of the hydram pump.